Dampak Pariwisata Cagar Budaya Candhi Cetho terhadap Komunitas Agama Hindu dan Kejawen - Devi Muslianty; Moh. Iqbal Ahnaf (UHN IGB Sugriwa Denpasar, 2018)
Does Cetho Temple need a status as a National Cultural Heritage if later it will only experience desacralization as a consequence of that status, which is then used by the government to manage the temple area as a tourist attraction? Although not recognized by the government on the grounds that there is no authentic evidence, the fact is that Cetho Temple is a place of worship not onlyfor Hindus but also Javanese who still hold the Kejawen tradition for generations. In addition, the Cetho Temple cultural tourism tour turned out to also give rise to contestation not only between religious communities but also government institutions that oversee Cetho Temple tourism management. From all that, the commodification of religious and cultural identity is also an important impact of Cetho Temple's cultural heritage tourism on the Hindu and Kejawen Communities. The qualitative research in this paper uses the Erving Goffman theory approach on